2008
DOI: 10.1080/20786204.2008.10873764
|View full text |Cite
|
Sign up to set email alerts
|

Improving the annual review of diabetic patients in primary care: an appreciative inquiry in the Cape Town District Health Services

Abstract: Background: Diabetes is a common chronic disease in the Cape Town District Health Services and yet an audit of diabetic care demonstrated serious deficiencies in the quality of care. The Metro District Health Services (MDHS) decided to focus on improving the annual review of the diabetic patient. The MDHS provides primary care to the uninsured population of Cape Town through a network of 45 Community Health Centres (CHC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 5 publications
0
28
0
Order By: Relevance
“…Although the predominant spoken language is isiXhosa, the recent population census revealed that other spoken languages include Setswana, isiZulu, English and Afrikaans (Lehohla, 2011). As is the case with other chronic conditions, epilepsy is managed in Community Health Centres (CHCs), which offer health care to most patients from low-socioeconomic groups (Mash, Levitt, Van Vuuren, & Martell, 2008). …”
Section: Methodsmentioning
confidence: 99%
“…Although the predominant spoken language is isiXhosa, the recent population census revealed that other spoken languages include Setswana, isiZulu, English and Afrikaans (Lehohla, 2011). As is the case with other chronic conditions, epilepsy is managed in Community Health Centres (CHCs), which offer health care to most patients from low-socioeconomic groups (Mash, Levitt, Van Vuuren, & Martell, 2008). …”
Section: Methodsmentioning
confidence: 99%
“…Findings from an annual review of diabetic patients in primary care in Cape Town reveal that there is a need for support groups in chronic illness care and management. The authors further state that support groups are an important strategy for increasing patients' self-efficacy [15]. A number of strategies that can be used for structured self-management interventions have been described internationally.…”
Section: The Role Of Epilepsy Support Groups and Self-managementmentioning
confidence: 97%
“…Health services provided include maternal and reproductive health, child health, TB, nutrition, school health, oral health, sexually transmitted infections (STI's), HIV, environmental health, mental health, rehabilitation services, and chronic illnesses (epilepsy, hypertension, asthma, and diabetes). Patients needing ambulatory care in CHCs are seen by clinical nurse practitioners and doctors [15]. Residents from these townships are of low socio-economic background and have high rates of illiteracy and unemployment [16].…”
Section: Participants and The Settingmentioning
confidence: 99%
“…Currently the education of diabetic patients and support of self-care has been left to the varied initiatives of individual health workers and there is no structured programme of education for people with diabetes in the Western Cape. Chronic care teams have identified that the health promoter should be the key person in delivering such a programme [7]. …”
Section: Introductionmentioning
confidence: 99%